2010
DOI: 10.1177/1548051810379798
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Use of Power Bases in a Model of Managerial Empowerment Practices and Employee Psychological Empowerment

Abstract: This paper explores the potentially central role that managers play in a model of empowerment. Issues of organizational goal accomplishment and employee trust often plague application of empowerment practices, and managers likely play a vital role in the successful implementation of empowerment. In this study, managerial use of power bases (reward, expert, referent, legitimate, coercive) was proposed to impact the relationship between managerial empowerment practices and employee psychological empowerment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 45 publications
5
61
0
2
Order By: Relevance
“…For example, Raven et al () grouped different types of power into hard and soft power bases. Randolph and Kemery () more broadly referred to expert and referent power as personal power, and legitimate, reward, and coercive power as position power. Lunenberg () combines these five power bases the same way but labels Randolph and Kemery's position power as organizational power.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Raven et al () grouped different types of power into hard and soft power bases. Randolph and Kemery () more broadly referred to expert and referent power as personal power, and legitimate, reward, and coercive power as position power. Lunenberg () combines these five power bases the same way but labels Randolph and Kemery's position power as organizational power.…”
Section: Resultsmentioning
confidence: 99%
“…Randolph and Kemery () recently reported updated alpha coefficients (N = 195) for the five power bases. Reward power (e.g., “influences how much a pay increase others may receive”) was reported to have an alpha coefficient of .74.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders are assumed to have a central role in the empowerment process of employees (Randolph & Kemery, 2011), whether through direct interventions and practices by the organization and managers or by psychological empowerment based on employee perceptions of their work role (cf. Spreitzer, 1995;Thomas & Velthouse, 1990).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Previous research has identified a positive association between EL and leader effectiveness (Tekleab et al, 2008) and favorable employee outcomes including performance (Vecchio, Justin, & Pearce, 2010), self-leadership (Amundsen & Martinsen, in press), psychological empowerment (Randolph & Kemery, 2011), job satisfaction (Konczak, Stelly, & Trusty, 2000), affective commitment (Dewettinck & van Ameijde, 2011), and creativity (Zhang & Bartol, 2010). However, several contingencies may theoretically affect such relationships, and one of these is self-other agreement (SOA), typically defined as the degree of congruence between a leader's self-rating and the ratings they receive from others (Yammarino & Atwater, 1993).…”
mentioning
confidence: 99%